2021
DOI: 10.3390/s21154949
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Maternal Physical Activities and Health Monitoring Using Wearable Sensors

Abstract: We propose a physical activity recognition and monitoring framework based on wearable sensors during maternity. A physical activity can either create or prevent health issues during a given stage of pregnancy depending on its intensity. Thus, it becomes very important to provide continuous feedback by recognizing a physical activity and its intensity. However, such continuous monitoring is very challenging during the whole period of maternity. In addition, maintaining a record of each physical activity, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 61 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…The findings ( Figure 2 ) revealed that 54 articles used motion tracking data in health care and physical wellness applications, of which 42 (78%) articles used motion-tracking sensors [ 75 - 81 , 84 - 86 , 88 - 97 , 101 , 103 - 116 , 119 , 121 - 123 , 125 , 126 ]. Overall, 70% (38/54) of the articles used AI technology combined with motion tracking data [ 75 , 77 , 79 , 82 - 85 , 87 , 89 - 91 , 93 , 94 , 97 , 99 - 101 , 103 , 105 , 106 , 108 , 109 , 111 - 113 , 117 - 128 ]. The role of AI mainly functions for data classification, monitoring, and visualization among the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The findings ( Figure 2 ) revealed that 54 articles used motion tracking data in health care and physical wellness applications, of which 42 (78%) articles used motion-tracking sensors [ 75 - 81 , 84 - 86 , 88 - 97 , 101 , 103 - 116 , 119 , 121 - 123 , 125 , 126 ]. Overall, 70% (38/54) of the articles used AI technology combined with motion tracking data [ 75 , 77 , 79 , 82 - 85 , 87 , 89 - 91 , 93 , 94 , 97 , 99 - 101 , 103 , 105 , 106 , 108 , 109 , 111 - 113 , 117 - 128 ]. The role of AI mainly functions for data classification, monitoring, and visualization among the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…1 Commercial grown of the Wearable Technology in the health care sector between 2015-2021 by [8] 2 DSR Methodology by [21] 3 Remote health monitoring system architecture proposed by [9] 4 Structure of body sensor nodes and the communication pathway by [13] 5 Design of an intelligent medical monitoring system by [13] 6 Framework Architecture by [15] 7 System Architecture by [17] 8 Examples of wearable devices used in health and cardiovascular disease by [45] 9 System Architecture and Structure 10 Hardware : Equipment used in this System 11 Data transfer/Message Protocols by [61] 12 MQTT Publish/Subscribe Model by [65] 13 Cluster Overview 14 Inserting times by [70] 15 Updating times by [70] 16 Deleting times by [70] 17 Command to run the program 18 Publish/Subscribe Methods 19 Average Velocity when walking and/or running by [74] 20 Speed distributions at different prescribed average speeds by [74]…”
Section: List Of Figuresmentioning
confidence: 99%
“…In more detail, a Python script with open-source code was used to establish communication between the shimmer sensors and the raspberry pi, allowing all sensor data to be sent to and stored on the raspberry pi local database . Like this study, there are other studies, such as [13] [14] [15] [16] [17], that employed different types of devices and approaches to achieve the similar goal of developing a healthcare remote system.…”
Section: Data Processing Used In Remote Health Monitoring Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous monitoring of pregnant women using wearable devices allows for the exploration of various pregnancy issues, such as stress 28,41 , hypertension 42 , mental problems 43 , and obesity 44 . Moreover, it enables the assessments of maternal sleep 45 , physical activity 46,47 , and fetal parameters, including heart activity [48][49][50] and movement 51,52 .…”
Section: Introductionmentioning
confidence: 99%